MO351CENTRE VARIATION IN MORTALITY FOLLOWING HOSPITAL-ACQUIRED ACUTE KIDNEY INJURY IN ENGLAND. (29th May 2021) - Peracha, Javeria; Pitcher, David; Santhakumaran, Shalini; Day, Jamie; Fotheringham, James; Steenkamp, Retha; Medcalf, James; Nitsch, Dorothea; Lipkin, Graham; McKane, William
Abstract: Background and Aims: Routine monitoring of outcomes for patients with Acute Kidney Injury (AKI) is necessary to drive quality improvement in AKI care. In this study, we describe development of a case-mix adjusted 30-day mortality indicator for patients with hospital acquired AKI (H-AKI), to facilitate identification of unwarranted variation in outcomes across hospitals in England. Method: We utilised a routinely collected national dataset of biochemically defined AKI cases, linked with hospitals administrative and mortality data. 250, 504 H-AKI episodes were studied in total, across 103 hospitals between January 2017 - December 2018. Standardised mortality ratios were calculated for each hospital using logistic regression; adjusting for age, sex, primary diagnosis, comorbidity score, AKI severity, month of AKI, and admission method. Results: Mean 30-day mortality rate was high at 28.6% and varied considerably between hospitals (22.3%-35.5%), with 23/103 trusts classed as outliers (95% control limits). Patients with H-AKI had mortality rates more than 5 times higher than the overall hospitalized population in 90/136 diagnosis groups and over 10 times higher in 60/136 groups. Increasing age, male sex, deprivation, higher comorbidity burden, more severe AKI stage at detection, emergency admission and admission during winter months were all associated with a higher risk of death Presentation at hospitals with on-site specialist nephrology services and Asian or Black ethnicity, however, were linked to a lower risk of death. Conclusion: This is the largest multi-centre analysis of mortality for patients with biochemically ascertained H-AKI to date, once again highlighting development of AKI as an important patient safety concern across hospital settings. Centres identified as having poor outcomes will need to carefully interrogate their AKI care pathways to understand and explore reasons underlying the observed variation to guide future quality improvement interventions.